The realization of thematic progressionin online ielts writing task 2 samples inan english-learning website: a case study = Phân tích sự tiến triển đề ngữ trong các bài mẫu IELTS Task 2 trực tuyến của một trang mạng học Tiếng Anh - Nguyễn, Văn Thắng (2020)
This research aims at investigating the frequency of Thematic Progression(TP) patterns and their effects on text quality of online IELTS Writing Task 2samples. Derived from an online website, the corpus consisting of 24 sample essays was analysed using both quantitative and qualitative methods as well as McCabe’s (1999) model of thematic progression. According to the results of this study, Simple Linear pattern is the most frequently employed one in the corpus, followed by Constant, Split Rheme, Split Theme and Derived Hyper theme pattern srespectively. Such order of frequency is generally in line with the existing literature, while that of Split Rheme is found to be considerably higher than in other studies. The analysis also shows that proper employment of TP overall is a contributing factor to the coherence and cohesion of the text, with each type exerting different effects. Simple Linear pattern, with its cross-referential links, yields a constantly developing and cohesive text whereas Constant Progression keeps a strong thematic focus. Meanwhile, Split Rheme and Split Theme pattern sare both found to offer a planned text development and Derived Hypertheme progression creates cohesion with hypernym-hyponym relation. Problems related to the overuse of the theme “It” and “There” are also reported from the corpus. Future research into this topic is recommended to investigate on a larger scale with the full range of essay genres and other aspects, for example the impact of L1 on TP in essays should be studied in depth as well.